2017
DOI: 10.7759/cureus.1247
|View full text |Cite
|
Sign up to set email alerts
|

Dermatitis Herpetiformis as the Initial Presentation of Primary Biliary Cholangitis in a Male with Gluten Sensitivity

Abstract: Celiac disease is commonly associated with elevated liver enzymes that normalize on a gluten-free diet. Celiac disease is rarely described in patients with primary biliary cholangitis. Dermatitis herpetiformis is the skin manifestation of the celiac disease that is very rarely associated with primary biliary cirrhosis. We present the case of a 62-year-old man who presented with severe chronic pruritus, in whom a diagnosis of primary biliary cholangitis was made initially. However, in the presence of atypical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The possibility of an association with skin autoimmune diseases such as psoriasis has been above mentioned[ 17 ]. A case report has shown that even dermatitis herpetiformis may occur[ 48 ].…”
Section: Skin Manifestationsmentioning
confidence: 99%
“…The possibility of an association with skin autoimmune diseases such as psoriasis has been above mentioned[ 17 ]. A case report has shown that even dermatitis herpetiformis may occur[ 48 ].…”
Section: Skin Manifestationsmentioning
confidence: 99%
“…Autoimmune disease clustering is very common in celiac disease; therefore, it is presumable that even NCGS could be associated with other autoimmune disorders [28]. Indeed, there are several reports in literature demonstrating connection with psoriasis, dermatitis herpetiformis [29,30], axial spondyloarthritis and connective tissue diseases [31].…”
Section: Discussionmentioning
confidence: 99%